2019
DOI: 10.1111/ijn.12743
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between work environment and career success among nurses with a master's or doctoral degree: A national cross‐sectional study

Abstract: Aims To investigate the career success and work environment among nurses with a master's or doctoral degree and analyse the effect of work environment on their career success. Methods This was a national descriptive, cross‐sectional study. A total of 1223 nurses with a master's or doctoral degree from 115 tertiary hospitals across mainland China participated in the study. Subscales of the practice environment scale of the nursing work index and career success scale were utilized for data collection via email i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
48
1
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(72 citation statements)
references
References 30 publications
8
48
1
15
Order By: Relevance
“…High total mean score of PES-NWI was significantly difference with higher educational level (master's degree), being working in the medical unit and having enough sleep hours and nurses with few years of working. The finding agreed with a study done in mainland China [16] with a total 1223 nurses with a master's or doctoral degree across 115 tertiary hospitals. The research revealed that work environment ratings of nurses were at a moderate level.…”
Section: Discussionsupporting
confidence: 90%
“…High total mean score of PES-NWI was significantly difference with higher educational level (master's degree), being working in the medical unit and having enough sleep hours and nurses with few years of working. The finding agreed with a study done in mainland China [16] with a total 1223 nurses with a master's or doctoral degree across 115 tertiary hospitals. The research revealed that work environment ratings of nurses were at a moderate level.…”
Section: Discussionsupporting
confidence: 90%
“…Achieving career success is defined as developing individual potential, meeting the satisfaction of growth needs, and realizing individual selfvalue (Woolston, 2019). Previous research on the career success of nurses mainly focused on either objective factors (Dan et al, 2018) or internally and externally driven factors (Wang et al, 2019). Among these, self-identity is an important psychological factor actively affecting career success (Arrowsmith et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Author details 1 People's Hospital of Deyang City, Deyang, Sichuan, China. 2 School of Nursing, Southwest Medical University, Dean of nursing school, Luzhou, China.…”
Section: Fundingmentioning
confidence: 99%
“…184 students from 11 provinces and cities in China completed this research. The exclusion criteria were: (1) students performing an international university exchange or clinical placements in other provinces at the time of the study, (2) questionnaires that were unintelligible, or in which no independent variable was selected. The Professional commitment scale: The level of professional commitment was measured by the Professional Commitment Scale, which is divied into four dimensions: affective commitment (9 items), continuance commitment (6 items), normative commitment (5 items), and ideal commitment (7 items).…”
mentioning
confidence: 99%